The Impact of Interest Rate Differentials, Digital Transformation, BOPO, and Promotional Funds on Third-Party Funds - Ika Merdekawati; Jacinta Winarto (Jurnal Informatika Ekonomi Bisnis, 2026)
The banking sector functions to mobilize and channel public funds, thereby maintaining national economic stability. In the post-COVID-19 era, the sector has faced intense competition in gathering public funds, also known as third-party funds. Despite this fierce competition, banks have actually experienced a significant increase in third-party funds, driven largely by the rapid growth of new digital banks. This surge in digital bank deposits suggests a migration of funds from conventional banks to digital banks. This study focuses on KBMI 2 banks, which are potentially the most directly affected by this shift of funds to digital banks. Digital banks offer several advantages, such as high deposit interest rates, digital services, greater efficiency, and attractive promotional offers. These advantages serve as a benchmark for KBMI 2 banks seeking to boost their third-party funds; the study examines factors including interest rate differentials, digital transformation, the BOPO ratio operating expenses to operating income, and promotional spending. The research employed panel data covering KBMI 2 banks listed on the Indonesia Stock Exchange from 2021 to 2025, using purposive sampling to select a sample of seven banks. Multiple linear regression analysis was used to examine the causal relationships between the independent and dependent variables. The results indicate that interest rate differentials 0.0043, digital transformation, and the BOPO ratio 0.0442 significantly influence third-party funds, whereas promotional spending 0.8936 does not. The recommended business strategy for KBMI 2 banks is to implement attractive deposit interest rates, adopt digitally transformed services, and maintain efficient operational performance to drive the growth of third-party funds.